Understanding the Shell Passivation in Ln3+‐Doped Luminescent Nanocrystals. Issue 3 (26th January 2022) - Shi, Rui; Brites, Carlos D. S.; Carlos, Luís D.
Abstract : Surface quenching is the main reason limiting the luminescence performance of Ln 3+ ‐doped nanocrystals and their practical applications. Although the shell passivation strategy effectively improves the luminescence efficiency, the understanding of the relevant passivation mechanisms remains elusive and contradictory explanations are often proposed. Herein, the context of debates on this topic is reviewed emphasizing that the discordant viewpoints are probably due to the lack of consideration of chemical disorders such as shell inhomogeneity, core–shell element intermixing, and inhomogeneous dopant distribution in the crystals. A clear awareness of the extent of these chemical disorders and their deleterious impact on the luminescence properties of the nanocrystals (intensified by the energy migration process) is crucial to avoid misinterpretations of the experimental findings. Abstract : A comprehensive understanding of shell passivation effect in Ln 3+ ‐doped luminescent nanocrystals is provided by considering the impacts brought by chemical disorders in the system that are normally overlooked, and a new perspective is proposed to evaluate the shell passivation efficiency in the general case.